HEALTH NUTRITION EDUCATION AND STRENGTHENING INDONESIAN CULTURE AMONG INDONESIAN MIGRANT WORKERS CHILDREN IN MALAYSIA - Rahmaddiansyah, Refa; Azizah, Aghasi Yanda Wafa; Abdurrahman, Adisa Muhammad; Muftiana, Sintya Nur; Haq, Addienul; Riswanti, Laila Wulan; Jalilah, Thurfah Hashifah; Masthurina, Ulfa; Hrp, Maritza Briliani Namora; Tambunan, Mega Intan; Pelani, Achmad Aziz; Noviar, Tita Falisha; Abdurrahman, Thariq; Azizah, Siti Nur (CV. Alina, 2024)
This service aims to improve children's understanding of balanced nutrition and promote their cultural awareness. The methods used in this program include integrated learning activities that focus on health education and cultural awareness. The materials used are from the